2007
DOI: 10.1021/jp0617930
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of Compressed 1,3,5,7-Tetranitro-1,3,5,7-tetraazacyclooctane (HMX), Cyclotrimethylenetrinitramine (RDX), 2,4,6,8,10,12-Hexanitrohexaazaisowurzitane (CL-20), 2,4,6-Trinitro-1,3,5-benzenetriamine (TATB), and Pentaerythritol Tetranitrate (PETN)

Abstract: Using the PW91, PBE, and LDA density functional theories (DFT), we have calculated crystal structures for five energetic molecular crystals over a range of experimental pressures. These crystals are 1,3,5,7-tetranitro-1,3,5,7-tetraazacyclooctane (HMX), cyclotrimethylenetrinitramine (RDX), 2,4,6,8,10,12-hexanitrohexaazaisowurzitane (CL-20), 2,4,6-trinitro-1,3,5-benzenetriamine (TATB), and pentaerythritol tetranitrate (PETN). Both PW91 and PBE generally overestimate volumes relative to experimental values, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
136
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 72 publications
(97 reference statements)
22
136
3
Order By: Relevance
“…21 A subsequent study demonstrated that an increase in pressure diminishes the importance of the dispersion interactions relative to the increasing contribution of the repulsive interactions. 22 As the external pressure applied to the simulation cell increased, the inaccuracies of the predicted intermolecular distances and lattice parameters relative to experimental data decreased, to the extent that good agreement with experiment was produced for pressures greater than 6-7 GPa. 21,22 Shimojo et al 24 have shown that the dispersion correction implemented by Grimme 25 accounts for the dispersion interactions accurately for the -RDX crystal in the high-pressure regime (0 -15 GPa), while incurring little additional computational overhead.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…21 A subsequent study demonstrated that an increase in pressure diminishes the importance of the dispersion interactions relative to the increasing contribution of the repulsive interactions. 22 As the external pressure applied to the simulation cell increased, the inaccuracies of the predicted intermolecular distances and lattice parameters relative to experimental data decreased, to the extent that good agreement with experiment was produced for pressures greater than 6-7 GPa. 21,22 Shimojo et al 24 have shown that the dispersion correction implemented by Grimme 25 accounts for the dispersion interactions accurately for the -RDX crystal in the high-pressure regime (0 -15 GPa), while incurring little additional computational overhead.…”
mentioning
confidence: 92%
“…22 As the external pressure applied to the simulation cell increased, the inaccuracies of the predicted intermolecular distances and lattice parameters relative to experimental data decreased, to the extent that good agreement with experiment was produced for pressures greater than 6-7 GPa. 21,22 Shimojo et al 24 have shown that the dispersion correction implemented by Grimme 25 accounts for the dispersion interactions accurately for the -RDX crystal in the high-pressure regime (0 -15 GPa), while incurring little additional computational overhead. In addition, the authors determined that the non-empirical van der Waals density-functional (vdW-DF) method also provides an accurate description of the vdW interactions, but requires orders-of-magnitude more computational resource.…”
mentioning
confidence: 92%
“…[1][2][3][4][5] Heating due to each of these mechanisms depends on the histories of the states of local stress and rate of deformation in the material. Existing literature examines the behavior of energetic crystals and polymer-bonded explosives (PBXs) in two general forms: as single crystals with anisotropic material properties, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and as heterogeneous collections of energetic grains with isotropic material properties. [23][24][25][26][27] The single crystal simulations have been carried out using both discrete methods (e.g., molecular dynamics (MD) and density functional theory (DFT)) [6][7][8][9][10][11][12][13][14][15][16] and continuum scale methods.…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature examines the behavior of energetic crystals and polymer-bonded explosives (PBXs) in two general forms: as single crystals with anisotropic material properties, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and as heterogeneous collections of energetic grains with isotropic material properties. [23][24][25][26][27] The single crystal simulations have been carried out using both discrete methods (e.g., molecular dynamics (MD) and density functional theory (DFT)) [6][7][8][9][10][11][12][13][14][15][16] and continuum scale methods. [17][18][19][20][21] Analyses utilizing discrete methods have yielded understanding of many of the thermo-mechanical properties of the polymorphs of HMX including crystal structure and lattice parameters, 11 isotherms, 10 elastic constants, 7 viscosity, 6 thermal conductivity, and behavior in compression.…”
Section: Introductionmentioning
confidence: 99%
“…Initial efforts focused on calculating equations of state (EOSs) and thermal properties using pure density functional theory (DFT) methods; however, DFT with generalized gradient approximation (GGA) greatly over-predicted equilibrium volumes by an average of 10% compared to experiment due to inadequate description of dispersive van der Waals (vdW) interactions [3,4]. More recently, attempts to economically incorporate vdW into DFT (DFT+vdW) led to various treatments using pair-wise C 6 r -6 potentials that are simply added to DFT at large distances [5,6].…”
Section: Introductionmentioning
confidence: 99%